Silver‐Mediated Squaric Acid Reduction as a Facile, Ambient‐temperature and Seedless Route to Tunable Bimetallic Au/Ag Nanostars and Nanosnowflakes. Issue 9 (10th August 2022) - Kist, Jennifer A.; Essner, Jeremy B.; Woodward, Jonathan D.; Baker, Gary A.
Abstract: Bimetallic Au/Ag nanoparticles were successfully synthesized using a facile and reproducible method involving rapid, room‐temperature mixing of aqueous solutions of HAuCl4 and AgNO3 in the presence of squaric acid as both the reducing agent and surface capping ligand. Variation in the initial Au : Ag molar ratio yielded a tunable anisotropic shape and affiliated surface plasmon resonance. The nanoparticles displayed excellent stability in water for at least 10 weeks and showed robust catalytic activity in the borohydride‐assisted reduction of the model substrate 4‐nitrophenol. Abstract : We report a simple, ambient‐temperature, and single‐pot route to bimetallic Au : Ag nanoparticles that employs squaric acid as the reducing and capping agent. Variation in the synthetic Au : Ag ratio reveals striking consequences for the nanoparticle morphology with related impact on the nanocatalytic activity toward nitroarene reduction.